DINAMIKA DAN TANTANGAN PANCASILA DALAM MASYARAKAT GLOBAL DAN DUNIA INTERNASIONAL - Amir Awaludin; Muhammad Khoiril Anam; Muhammad Uchaida Sabilil Matin; Muhammad Fikri Abdun Nasir (STKIP Pesisir Selatan, 2026)
The phenomenon of globalization, characterized by the rapid flow of ideologies, cultures, information, and technologies across national boundaries, presents significant challenges to the preservation and actualization of Pancasila values in the context of international society. The expansion of liberalism, individualism, and materialism often marginalizes collective values, potentially weakening national identity, social solidarity, and moral orientation within Indonesian society. In response to these dynamics, this study aims to analyze the challenges and transformations faced by Pancasila values amid globalization and to examine their relevance and strategic role at the global level. This research adopts a qualitative approach through a literature review method, drawing upon scientific journals, books, and relevant academic publications. The findings indicate that Pancasila remains a flexible and adaptive open ideology capable of functioning as a cultural filter against negative global influences, while simultaneously serving as a foundation for ethical universalism and normative guidance in international relations. Furthermore, Pancasila contributes to shaping Indonesia’s moral diplomacy by promoting values of humanity, justice, tolerance, and peace. The study concludes that strengthening value-based education and contextualizing the implementation of Pancasila in contemporary global discourse are essential to maintaining its relevance and reinforcing Indonesia’s identity in the era of globalization.